2012
DOI: 10.3390/molecules17032378
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics, Flavonoids, Antioxidant Activity and Cyanogenic Glycosides of Organic and Mineral-base Fertilized Cassava Tubers

Abstract: A field study was conducted to determine the effect of organic and mineral-based fertilizers on phytochemical contents in the tubers of two cassava varieties. Treatments were arranged in a split plot design with three replicates. The main plot was fertilizer source (vermicompost, empty fruit bunch compost and inorganic fertilizer) and sub-plot was cassava variety (Medan and Sri Pontian). The amount of fertilizer applied was based on 180 kg K 2 O ha −1. The tubers were harvested and analyzed for total flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 16 publications
2
41
2
5
Order By: Relevance
“…The biosynthesis of phenolic composition of berry fruits can be endogenously‐regulated during different developmental variations, which can be affected by exogenous agents. Various exogenous factors such as environmental conditions (temperature, biotic and abiotic stress, light intensity, humidity) and agricultural practices (soil fertility, irrigation) influence phenolic compound biosynthesis and accumulation in medicinal plants . Amino acid phenylalanine, produced through the shikimic acid pathway, is a precursor for several phenolic compounds.…”
Section: Resultsmentioning
confidence: 77%
“…The biosynthesis of phenolic composition of berry fruits can be endogenously‐regulated during different developmental variations, which can be affected by exogenous agents. Various exogenous factors such as environmental conditions (temperature, biotic and abiotic stress, light intensity, humidity) and agricultural practices (soil fertility, irrigation) influence phenolic compound biosynthesis and accumulation in medicinal plants . Amino acid phenylalanine, produced through the shikimic acid pathway, is a precursor for several phenolic compounds.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, another study reported amounts of the flavonoids quercetin and kaempferol in Rosa species between 3.68 ( R. agrestis ) and 15.81 mg g −1 DW ( R. gallica ) and between 1.25 ( R. subcanina ) and 9.41 mg g −1 DW ( R. caryophyllacea ) respectively . The differences observed in phenolic compounds between different Rosa genotypes can be related to genetic diversity of species, geographical origin and environmental stresses . In addition to environmental conditions that have considerable effects on the biosynthesis of secondary metabolites such as phenolic compounds, genetic factors can also participate in the biosynthesis and accumulation of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, very little information regarding the managing irrigation and N fertilisation of winter wheat for high antioxidants content is available. The studies on vegetable and medical plant showed that fertilisation and irrigation have significantly influenced on phenolic compounds and carotenoid content . The results of Alizadeh et al showed that the use of mineral fertiliser increased total phenolic content and antioxidant activity in Satureja hortensis .…”
Section: Introductionmentioning
confidence: 99%